197k views
15 votes
Csc A - sin A =

A. (cos^2A) / (sinA)
B. (1 - sinA) / (sinA)
C. (1 - sinA) / (cosA)

Csc A - sin A = A. (cos^2A) / (sinA) B. (1 - sinA) / (sinA) C. (1 - sinA) / (cosA-example-1
User Brisi
by
4.9k points

2 Answers

11 votes

Answer:

1st option

Explanation:

Using the identities

csc x =
(1)/(sinx)

sin² x + cos²x = 1 ⇒ cos²x = 1 - sin²x

then

csc A - sinA

=
(1)/(sinA) - sinA

=
(1-sin^2A)/(sinA)

=
(cos^2A)/(sinA)

User Artanik
by
4.6k points
6 votes

Answer:

A)
(cos^2A)/(sinA)

Explanation:


cscA-sinA\\\\(1)/(sinA)-sinA\\ \\(1)/(sinA)-(sin^2A)/(sinA)\\ \\ (1-sin^2A)/(sinA)\\ \\(cos^2A)/(sinA)

User ChrisMacSEA
by
4.2k points